Gambaran Kohesivitas Kelompok Teman Sebaya Pada Anggota Komunitas City Bike (CB) Icikiwir Dikota Solo Raya - Rantri Mustika Dewi; Dhian Riskiana Putri; Anniez Rachmawati Musslifah (Pusat Riset dan Inovasi Nasional, 2025)
Group cohesiveness refers to the strong sense of solidarity and unity within a group, reflected through positive interactions, frequent time spent together, and high collective morale. This study aims to explore and describe the group cohesiveness of the Icikiwir motorcycle community members in the Solo area. A qualitative research approach was employed, utilizing in-depth interviews and direct observations involving nine informants, consisting of both members and leaders of the community. The Icikiwir City Bike Motorcycle community was formed not only for recreational purposes but also to establish meaningful social networks, expand friendships, enhance mutual respect, foster cooperation, and increase members’ self-confidence. The findings of this study revealed that six out of the nine informants exhibited strong group cohesiveness. These members actively participated in various community activities, demonstrated loyalty, and worked collaboratively to achieve group objectives. Their involvement contributed to creating a supportive and friendly environment within the community. Conversely, one member showed poor group cohesiveness due to a lack of engagement and minimal attendance in group events. This individual had weaker social bonds with other members, which impacted his sense of belonging. Meanwhile, the two community leaders demonstrated excellent cohesiveness by consistently supporting and embracing all members. Their leadership played a pivotal role in strengthening group unity and promoting inclusiveness. The study concludes that active participation, mutual trust, and inclusive leadership significantly contribute to the development and sustainability of group cohesiveness. These findings underscore the importance of social interaction and shared goals in building a strong, cohesive community, particularly in informal social groups such as motorcycle communities.